How Parenting Courses Affect Families' Time-Use? Evidence from an RCT Experiment in Italy - Daniela Del Boca; Chiara D. Pronzato; Lucia Schiavon (Institute of Labor Economics (IZA), 2022)
This paper investigates the impact of parenting courses on families' time use with their children in urban areas in Italy. Courses aimed at raising parental awareness of the importance of educational activities were offered in four cities (Naples, Reggio Emilia, Teramo and Palermo) within the framework of the social program "FA.C.E. Farsi Comunità Educanti". In order to conduct the impact evaluation, we designed a randomized controlled trial involving random assignment of the families (mostly mothers). At the end of the intervention, we administered an assessment questionnaire both to the treatment group, which took the course, and to the control group, which did not. Comparing the outcomes, we find that attending the course increased families' awareness of the importance of educational activities for children, reading often to the children and spending more time with them.
Keywords: J13; D1; I26; 330; parenting; use of time; educational activities; randomized controlled trial